Formation of Geometric Patterns in the Architectural Decoration: An Investigation on the Ilkhanids’ Period - Rajabi, Fatemeh; Khosravi, Molood (Journal of History Culture and Art Research, 2019)
The Ilkhanids made considerable changes in their ancestors’ legacy after capturing Iran caused the creation of complex geometric patterns. Exhaustive research has been undertaken about the features of decoration of this era; however, the raised question is how this progress could have happened in spite of slaughtering or secluding the artists. The purpose of this study is to point out the role of the most effective factors in the formation of the decorations with complex geometric patterns during the Ilkhanids’ era. This study implements a descriptive-historical approach with reference to written library sources. The analysis of the observations shows that Iranian rulers and scholars, especially Nasir al-Din Tosi, have played a key role in this development. This includes especially Nasir al-Din Tosi who is the composer of several fields including astronomy, ethics, history, logic, jurisprudence, mathematics, medicine, poetry, and philosophy as well he translated from the Greek geometry books. His success influenced Mongols. Eventually, he was appointed in several administration positions. His position influenced the promotion and progress of the geometry and math and their application in architecture and engineering. In fact, it can be said that the interaction of architects and mathematicians, which was Tosi’s brainchild, brought about a turning point in the Ilkhanids’ art and architecture, especially geometric decorations.